ChemInform Abstract: Catalytic Activation of a Single C—F Bond in Trifluoromethyl Arenes. Issue 18 (April 2016) - Dang, Hester; Whittaker, Aaron M.; Lalic, Gojko
Abstract: An optimized combination of a Pd and a Cu catalyst allows the selective monodefluorination of the title compounds under mild conditions.